Generation of biometric sequence using real time electrocardiogram signal - SRIKANTH MADIREDDY; MOHANA.J; C.KEERTHIKANTH; P. SRIHARI REDDY (International Journal of Pharma and Bio Sciences, 2017)
The prime aim of the paper is to generate a biometric key using real time electrocardiogram (ECG) signal. The advancement of body area network made the patient to be treated from anywhere. In such networks, it is important to see the data is authorized by the specific person. The data should be monitored to remain protected. To transmit the data from one node to another node or from one node to master node the data should be encrypted. For encryption, there should be key. In this paper, a key will be developed using real time electrocardiogram signal. From one person to another person the heartbeat will differ. RR variability where R is a point corresponding to the peak of QRS complex of the ECG wave and RR is the interval between successive RS and heart period variability. From the ECG wave the RR intervals are extracted and the difference between the RR intervals is taken and it is converted into binary format. By considering the ECG signal of different persons different keys can be developed and it will be random. These randomly generated ECG sequences can be used as security keys for encryption or authentication in a WBAN system.